SIMULASI MANAJEMEN RISIKO REPUTASI BANK SYARIAH - Hasibuan, Muhammad Rizal; Santoso, Muhammad Rifky; Siregar, Saparuddin (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2023)
Islamic Bank operations meet various risks and one of them is reputation risk. The reputation of Islamic banks can be profitable and harmful. Therefore, Islamic Banks need to mitigate the risks so that this reputation can have a beneficial impact on Islamic banks. This article discusses the meaning of Islamic bank reputation and what factors influence the reputation risk. The reputation of Islamic banks is a collection of images from stakeholders towards Islamic banks. This reputation does not stand alone and is influenced by other things such as liquidity. The reputation risk of Islamic banks is influenced by 5 things, namely the owner's reputation, business ethics, products and business processes, negative publicity, and customer complaints. In order to mitigate this risk, it is necessary to apply an assessment by implementing risk management.